A trial studying approach to predict college achievement - Meijer, Rob R.; Niessen, A. Susan M. (Frontiers in Psychology, 2015)
We argue that using trial studying is a reliable and valid way to select students for higher education. This method is based on a work sample approach often used in personnel selection contexts. We discuss that this method has predictive validity for study success, has high acceptance by stakeholders, and measures self-regulation in a high-stakes testing context that cannot be measured through self-report questionnaires. We suggest further research to implement this method to select students.